Orally Disintegrating Tablets: An Overview - Evren ALÄžIN YAPAR (Journal of Applied Pharmaceutical Science, 2014)
Orally disintegrating tablets (ODTs) have greatly increased dosage forms which have remarkable impact on the patient compliance especially for the pediatric, geriatric and psychiatric patients with deglutition disorders. Several technologies either conventional or patented based on freeze drying/lyophilization, spray drying, moulding, phase transition process, melt granulation, sublimation, mass extrusion, cotton candy process, direct compression etc. have been developed for manufacturing of ODTs. In this review brief information about ODTs including definition, ideal and desired characteristics, advantages, limitations and disadvantages, drug canditates, challenges in formulation, excipients with recent developments in superdisintegrants, tast masking, manufacturing techniques, evaluation parameters and recent patents in ODTs are presentented.
Keywords: Deglutition disorders, orally disintegrating tablets, excipients, taste masking, patents.